TOTAL PHENOLIC, CONDENSED TANNINS, ASCORBIC ACID CONTENTS AND FREE RADICAL SCAVENGING ACTIVITY IN SOME OF THE UNDERUTILIZED HORTICULTURAL CROPS FROM NORTH-WESTERN INDIAN HIMALAYAS - R. S. PAL, R. ARUN KUMAR, CHANDRASHEKARA, C., N. K. HEDAU, P. K. AGRAWAL; J. C. BHATT (The Bioscan, 2013)
Mature fruits of F. roxburghii and F. daltoniana, areal bulbils of D. kumaunensis and roots of P. acinosa were collected from Uttarakhand, India and were evaluated for their total phenolics, condensed tannins, ascorbic acid (Vita C) and Free radical scavenging activities against DPPH•, ABTS•+ and Hydrogen peroxide (H2O2) free radicals. Total phenolics varied between 9.24-16.92 mg TA/g, catechins between 1.31-5.03 mg/g, ascorbic acid between 35.80-63.69 mg/100g. Methanolic extracts of F. roxburghii showed maximum percent scavenging activities on DPPH and ABTS radical while H2O2 scavenging activity was observed highest in D. kumaunensis. IC50 values for radical scavenging assays of methanolic extracts were calculated and found that in terms of antioxidant activities, F. roxburghii showed maximum followed by D. kumaunensis and minimum was by P. acinosa. Multifactorial comparisons using principal component analysis (PCA) was done and found that F. daltoniana possessed higher ascorbic acid content, while F. roxburghii possessed higher total phenolics, condensed tannin and free radical scavenging activities then others studied plant samples. Results of the finding provides evidence that the crude methanolic extract of the studied underutilized horticultural crops are valuable source of natural antioxidant, which can be applied in both healthy medicine and food industry.